IMPROVEMENT OF ECG SIGNALS ANALYSIS BASED ON WAVELET CONVERSION IN HIGH-RESOLUTION ELECTROCARDIOGRAPHY SYSTEM - Dubrovin, V. I.; Tverdokhleb, U. V. (Radio Electronics, Computer Science, Control, 2011)
In this paper we present an improved method of ECG signals delineation based on continuous wavelet conversion and single-scale approach. The algorithm permits to detect nine reference points in all ECG parts: onset, peak and offset of T wave, QRS complex and P wave. The implemented algorithm significantly increases the accuracy of P wave and T wave detection, which was the problem of the previous methods. We propose also the improved method of ECG signals filtering from noise as updating of the wavelet-thresholding methods.